Structure evolution in poly(ethylene-co-vinyl alcohol)/lignin blends: Effect of interactions and composition. (February 2019) - Pregi, Emese; Kun, Dávid; Vu, Vi; Pukánszky, Béla
Graphical abstract: Highlights: Lignin and ethylene-vinyl alcohol copolymers form heterogeneous blends. Particle break-up and coalescence determine the size of dispersed lignin particles. Coalescence of particles is determined by composition and component interactions. Thermodynamic factors are stronger than kinetic ones in the studied system. A semi-empirical model was proposed to describe the correlation of variables. Abstract: Blends were prepared from lignin and ethylene-vinyl alcohol (EVOH) copolymers to study the effect of component interactions and composition on structure. The vinyl alcohol (VOH) content of the polymers changed between 0 and 76 mol%, while the lignin content of the blends varied between 0 and 60 vol%. Low density polyethylene (LDPE) with 0 mol% VOH content was used as reference. The components were homogenized in an internal mixer and the dispersed structure of the blends was characterized by scanning electron microscopy (SEM). As an effect of the strong self-interactions of lignin, this latter forms immiscible blends with ethylene-vinyl alcohol copolymers in spite of the hydrogen bonds acting between the two components. Because of immiscibility, lignin is dispersed in the form of particles in the EVOH phase even at lignin contents as large as 60 vol%. The size of dispersed lignin particles is determined by particle break-up and coalescence, the original lignin particles of around 80 μm size break up to much smaller ones; particle sizes below one micrometer form at large vinyl alcohol contents. As equilibrium thermodynamic factors are stronger than kinetic ones in the studied system, changing shear stresses do not influence particle size much. The coalescence of particles is determined by composition and component interactions, and a simple semi-empirical model was proposed to describe the correlations of these variables quantitatively. Good agreement was found between the prediction of the model and experimental results.